Disinformation and Cyber Operations in the Russia–Ukraine War: A Systematic Review of Threats, Mechanisms, and Countermeasures in a Globalized Media Ecosystem - Melnyk, Viktor; Babenko, Lyudmyla; Dzhahunova, Olena; Balycheva, Larysa; Fedotova, Oksana (Asian Journal of Interdisciplinary Research, 2026)
The study aims to analyze the impact of globalization on Ukraine’s information security from a historical perspective and to identify key challenges and directions for strengthening national resilience in the information domain. The study is based on a structured literature search and qualitative content analysis of scientific sources. Content analysis is conducted to examine academic literature on the evolution of Ukraine’s information security under globalization.The findings demonstrate that after the collapse of the USSR, Russian media actively shaped Ukrainian audiences through Moscow-centered narratives. Effective countermeasures emerged only in 2014, while the full blocking of Russian information channels after February 24, 2022, became a crucial step in safeguarding national information security. Key challenges identified include cyber threats, information aggression, unequal access to digital resources, regulatory gaps, and the lack of comprehensive international cooperation. Strengthening Ukraine’s information security in the era of globalization requires enhanced cyber defense, the development of media literacy, the adoption of advanced protection technologies, and the implementation of regional security initiatives. Active collaboration with international partners and the integration of modern technologies are essential to ensuring a sustainable and secure information environment.